Zeolitic Imidazolate Framework-67-Derived NiCoMn-Layered Double Hydroxides Nanosheets Dispersedly Grown on the Conductive Networks of Single-Walled Carbon Nanotubes for High-Performance Hybrid Supercapacitors - Yingying Li; Qin Zhou; Yongfu Lian (Nanomaterials)
A supercapacitor’s energy storage capability is greatly dependent on electrode materials. Layered double hydroxides (LDHs) were extensively studied as battery-type electrodes because of their 2D structure and quick intercalation/deintercalation of electrolyte ions. However, the energy storage capability for pristine LDHs is limited by their large aggregation tendency and poor electrical conductivity. Herein, a novel NiCoMn-LDH/SWCNTs (single-walled carbon nanotubes) composite electrode material, with ultrathin NiCoMn-LDH nanosheets dispersedly grown among the highly conductive networks of SWCNTs, was prepared via a facile zeolitic imidazolate framework-67 (ZIF-67)-derived in situ etching and deposition procedure. The NiCoMn-LDH/SWCNTs electrode demonstrates a specific capacitance as large as 1704.3 F g−1 at 1 A g−1, which is ascribed to its exposure of more active sites than NiCoMn-LDH. Moreover, the assembled NiCoMn-LDH/SWCNTs//BGA (boron-doped graphene aerogel) hybrid supercapacitor exhibits a superior capacitance of 167.9 F g−1 at 1.0 A g−1, an excellent energy density of 45.7 Wh kg−1 with a power density of 700 W kg−1, and an outstanding cyclic stability with 82.3% incipient capacitance maintained when subjected to 5000 charge and discharge cycles at the current density of 10 A g−1, suggesting the significant potential of NiCoMn-LDH/SWCNTs as the electrode material applicable in supercapacitors.